2020
DOI: 10.1021/acs.chemmater.0c02602
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Hydroxyl Anions Promotes Lithium Ion Conduction in Antiperovskite Li2OHCl

Abstract: Li 2 OHCl is an exemplar of the antiperovskite family of ionic conductors, for which high ionic conductivities have been reported, but in which the atomic-level mechanism of ion migration is unclear. The stable phase is both crystallographically defective and disordered, having ∼1/3 of the Li sites vacant, while the presence of the OH − anion introduces the possibility of rotational disorder that may be coupled to cation migration. Here, complementary experimental and computational methods are applied to under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
89
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 64 publications
(96 citation statements)
references
References 39 publications
7
89
0
Order By: Relevance
“…Copyright 2020, American Chemical Society. 63 SSEs, solid-state electrolytes phase, as shown in Figure 3C. It indicated that the H movement in the orthorhombic phase is much slower than that in the cubic phase.…”
Section: Dynamics Of H or Oh Group In Lithium Halide Hydroxidesmentioning
confidence: 89%
See 2 more Smart Citations
“…Copyright 2020, American Chemical Society. 63 SSEs, solid-state electrolytes phase, as shown in Figure 3C. It indicated that the H movement in the orthorhombic phase is much slower than that in the cubic phase.…”
Section: Dynamics Of H or Oh Group In Lithium Halide Hydroxidesmentioning
confidence: 89%
“…The MD simulations showed that the lower coordination of oxygen with Li corresponds to the faster the movement of the proton due to the larger space left for the movement of the proton. 63 Additionally, the dynamics behavior of the proton and Li in the cubic Li 2 OHCl has been studied by Dawson et al 64 The MD simulations demonstrated that the protons can just locally move around the O atoms in the center of the octahedron, thus they do not participate in the long-distance diffusion. In contrast, the Li + can diffuse in the whole lattice.…”
Section: Dynamics Of H or Oh Group In Lithium Halide Hydroxidesmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, we point out that anion rotational disorder and highly concerted local cation mobility operate in tandem within the so-called ‘paddlewheel mechanism’, which has been widely discussed in the literature [ 72 , 88 , 93 , 95 , 105 112 ]. Although this term is sometimes invoked to describe any type of anion rotation dynamical frustration, in our view this definition is too liberal.…”
Section: Dynamical Frustrationmentioning
confidence: 94%
“…Theoretical and experimental investigations into Li 2 OHCl have provided solid evidence of a conductivity jump related to a paddlewheel mechanism. Li 2 OHCl is stable in the orthorhombic phase at room temperature and transitions to the cubic phase at 38 °C. ,,, The phase transition is accompanied by an increase in ionic conductivity from 1.2 × 10 –8 S cm –1 at 37 °C to 1.4 × 10 –6 S cm –1 at 39 °C . Above the transition, its ionic conductivity is similar to Li 2 OHBr, which is cubic at all temperatures. , Eilbracht et al establish with neutron powder diffraction of Li 2 ODCl that OD is static in the low-temperature orthorhombic phase but can point to different octahedral faces in the cubic phase .…”
Section: Ion Conduction Mechanismsmentioning
confidence: 99%